Inside money, investment, and unconventional monetary policy - Lukas Altermatt (University of Zurich, Department of Economics, 2019)
I develop a model that explicitly takes the role of financial institutions in the transmission mechanism of monetary policy into account. Within this model, I find various equilibrium environments, with one of them resembling a standard environment for monetary policy and another one akin to a liquidity trap. I analyze what the effects of various monetary policy measures such as quantitative easing, open-market operations, helicopter money and negative interest rates are in all of these environments. I find that open-market operations, quantitative easing, and negative interest rates on reserves are powerless in a liquidity trap, while helicopter money can be used to increase investment. The model also shows that a floor system allows a central bank to implement monetary policy with less side effects, but at the cost of losing control over inflation through open-market operations.
Keywords: E43; E52; E63; G21; H63; 330; new monetarism; liquidity trap; helicopter money; negative interest rates; government debt; Ricardian equivalence; banking; floor vs channel system